Conceptualization and Evaluation of a School Project on Climate Science in the Context of Education for Sustainable Development (ESD) - Mareike Schauss; Sandra Sprenger (MDPI AG, 2019)
Anchored in the thirteenth of the Sustainable Development Goals (SDG), climate change is one of the key content areas in education for sustainable development. This evaluation study describes a school project that introduces students to scientific work and, more specifically, to scientific research methods in climate research. Using a pre-post design, the evaluation uses a scale measuring epistemological beliefs, as well as two other scales addressing the relevance of climate change in society and career prospects in the field of climate research. The quantitative questionnaire data indicate an increase in future career aspirations in the field of climate research. The qualitative interview data reveal positive changes in the understanding of science and show that an understanding of the nature of science can be promoted.